The effects ofesterified glucomannan on some biochemical parameters during experimental aflatoxicosis in japanese quails - Banu ATALAY; Zafer DURGUN (Eurasian Journal of Veterinary Sciences)
ln this study it was aimed to determine protective effects of different doses (1 g/kg and 2 g/kg feed GM) esterified glucomannan (GM) against to experimentally chronic aflatoxicosis (1 mg/kg feed AF) in Japanese quails (Coturnix coturnix japonica). In this study, 10 day old, healthy 240 male Japanese quails were used. These animals were separated equally into six groups. These groups were fed with normal diet (K), the same diet containing 2 mg/kg aflatoxin (AF), 1 g/kg GM (GM1), 2 g/kg GM (GM2), 2 mg/kg aflatoxin + 1 g/kg GM (AF+GM1) and 2 mg/kg aflatoxin + 2 g/kg GM (AF+GM2) for 42 days. In the blood samples taken on the 21st and 42nd day. it was determined decrease in total protein (TP), albumin, tryglyseride, cholesterole, glucose, calcium (Ca). inorganic phosphorus (IP), and blood urea nitrogen (BUN) levels and increase in alanineaminotransferase (ALT) and aspartatearninotransferase enzymes activities in the AF ve AF+GM1 groups (P<0.05). TP, albumin, tryglyseride, cholesterole, glucose and BUN levels with ALT and AST activities in the group which administrated 2 g/kg dose GM as adsorbent were significantly different (P<0.05) than that of AF and 1 g/kg GM treatment groups and similar to control group levels. Present study demostrated that of 1 g/kg dose GM application as protective hadn't positive effects while 2 g/kg dose GM treatment caused beneficial effects in respect of many parameters in aflatoxicosis